Increase in skin perfusion pressure predicts amputation-free survival after lower extremity bypass surgery for critical limb ischemia. (June 2018) - Yamamoto, Kota; Kawahara, Takuya; Akai, Atsushi; Isaji, Toshihiko; Akagi, Daisuke; Miyahara, Takuya; Hoshina, Katsuyuki
The objective of this study was to determine how postoperative skin perfusion pressure (SPP) as a measure of blood flow after revascularization affects limb prognosis in patients with critical limb ischemia (CLI). We retrospectively reviewed 223 consecutive bypass surgery cases performed in 192 patients with CLI during a 10-year period. SPP was measured 1–2 weeks before and after the procedure. An SPP of 40 mmHg was set as the cut-off value for revascularization. Patients were grouped according to their postoperative SPPs, and amputation-free survival (AFS) was analyzed. An SPP of ≥ 40 mmHg was recovered in 75% of the patients, but no significant difference was found between this group and the group that did not reach 40 mmHg. On the other hand, the values increased by ≥ 20 mmHg from the preoperative values in 70% of the patients. This group had a significantly better AFS than the group that did not increase by 20 mmHg. Logistic regression analysis revealed that (1) a preoperative SPP of < 20 mmHg and (2) a high serum albumin level (> 3.0 g/dL) were significant factors in increasing SPP by 20 mmHg. These results showed that an increase in SPP of ≥ 20 mmHg after bypass surgery was associated with better limb prognosis.